2004
DOI: 10.2136/sssaj2004.1326
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Soil Line Identification Routine for Remotely Sensed Images

Abstract: The soil line is a linear relationship between the near‐infrared (NIR) and red (R) reflectance of bare soil as characterized by slope and intercept parameters. Vegetation indices use soil line parameters extensively in crop growth analyses. Research indicates that the soil line can be related to site‐specific soil conditions within a field, especially organic C content. This relationship may provide a means for directing soil sampling. However, these soil and crop growth remotely sensed predictions require acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…Among these soil-adjusted vegetation indices, the TSAVI, ATSAVI, and PVI were developed to minimize soil background influence by incorporating the slope and intercept of the soil line, which was established by linear regression of soil reflectance in red-NIR spectral portions. Compared with the soiladjusted SAVI, MSAVI, OSAVI, and GSAVI, the algorithms of TSAVI, ATSAVI, and PVI containing the soil line parameters greatly limit their applications due to the difficulty of obtaining the real soil line [Baret et al, 1993;Fox et al, 2004;Liu et al, 2008]. The contribution of the litter is another prominent barrier to the determination of green aboveground biomass in arid and semiarid grassland, where the litter is a large vegetation component [Van Leeuwen and Huete, 1996;Asner et al, 1998;Guo, 2002;He et al, 2006;Ren and Zhou, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Among these soil-adjusted vegetation indices, the TSAVI, ATSAVI, and PVI were developed to minimize soil background influence by incorporating the slope and intercept of the soil line, which was established by linear regression of soil reflectance in red-NIR spectral portions. Compared with the soiladjusted SAVI, MSAVI, OSAVI, and GSAVI, the algorithms of TSAVI, ATSAVI, and PVI containing the soil line parameters greatly limit their applications due to the difficulty of obtaining the real soil line [Baret et al, 1993;Fox et al, 2004;Liu et al, 2008]. The contribution of the litter is another prominent barrier to the determination of green aboveground biomass in arid and semiarid grassland, where the litter is a large vegetation component [Van Leeuwen and Huete, 1996;Asner et al, 1998;Guo, 2002;He et al, 2006;Ren and Zhou, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…The above result, (19), is one of the objectives of this paper. It indicates two facts: (1) The slope of the vegetation isoline is linearly correlated to the amount of difference in the soil line slope, ∆a, (independent of difference in the offset, ∆b); (2) The offset of the vegetation isoline is linear correlated to both ∆a and ∆b in opposite ways (one negative and the other positive).…”
Section: Derivation Of Soil Line Influce On Vegetation Isolinementioning
confidence: 90%
“…Although many studies reported general values of a and b, these two parameters depend on chemical and mineral contents, proportion of organic matter, soil moisture, and hence these are unique to individual soil type [15,19,23,31,32]. It is also known that these parameters vary with band position and band width properties of a multispectral sensor [12,[33][34][35], indicating the uniqueness of these parameters to each sensor.…”
Section: Soil Line Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…This information has intensively been used for characterization of the earth's surface for retrievals of vegetation biophysical parameters [4][5][6][7][8][9][10][11][12] and soil surface status [13][14][15][16][17][18] from remotely sensed reflectance spectra. Several studies have indicated that the soil moisture and organic matter contents relate to changes in soil reflectance along the soil line [2,14,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%